(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the role of investments in green technologies in achieving sustainable development through the information technology sector. The IT sector is considered a crucial factor in increasing energy efficiency, reducing waste, and ensuring environmental sustainability through innovative solutions. The article discusses best practices, challenges, and solutions to improve investment efficiency.